Personal Branding Melalui Rational Emotive Behavior Therapy Untuk Meningkatkan Kebermaknaan Hidup - Azzahra, Ajeng Suci; Japar, Muhammad; Lianasari, Dewi (Universitas PGRI Madiun, 2023)
The meaning of life is one of the important things in an individualsâ€™s life. The meaning of life can be increased through several efforts, one of which is by maximing the abilities, potential, and talents possessed, including developing personal branding.Â The purpose of this study is to assist individuals in developing personal branding through Rational Emotive Behavior Therapy to increase the meaning of life. The research methoud use is a pre-experimental one group pretest posttest design with a sampling technique that is simple random sampling. The result showed that group counseling for the development of personal branding thrrough Rational Emotive Behavior Therapy was effective in increasing the meaning of life, that the significance value asymp sig (2-tailed) of Paired Sample T-test is 0,001 < 0,05.